2016
DOI: 10.1007/s00208-016-1466-2
|View full text |Cite
|
Sign up to set email alerts
|

Small Lefschetz fibrations and exotic 4-manifolds

Abstract: Abstract. We explicitly construct genus-2 Lefschetz fibrations whose total spaces are minimal symplectic 4-manifolds homeomorphic to complex rational surfaces CP 2 #p CP 2 for p = 7, 8, 9, and to 3CP 2 #q CP 2 for q = 12, . . . , 19. Complementarily, we prove that there are no minimal genus-2 Lefschetz fibrations whose total spaces are homeomorphic to any other simply-connected 4-manifold with b + ≤ 3, with one possible exception when b + = 3. Meanwhile, we produce positive Dehn twist factorizations for severa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
48
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(50 citation statements)
references
References 53 publications
2
48
0
Order By: Relevance
“…By modifying the 4-chain relation, Baykur and Korkmaz [1] found an interesting relation in M 1 2 . In the following we lift the Baykur-Korkmaz relation (a relation which is obtained from Equation (3.1) below by capping off the boundary circle δ 0 with a disk) to M 2 2 , and using this lift we improve the upper bounds for N (3,1) and N (4, 1).…”
Section: Theorem 31 ([12]) For the Minimal Numbermentioning
confidence: 99%
See 2 more Smart Citations
“…By modifying the 4-chain relation, Baykur and Korkmaz [1] found an interesting relation in M 1 2 . In the following we lift the Baykur-Korkmaz relation (a relation which is obtained from Equation (3.1) below by capping off the boundary circle δ 0 with a disk) to M 2 2 , and using this lift we improve the upper bounds for N (3,1) and N (4, 1).…”
Section: Theorem 31 ([12]) For the Minimal Numbermentioning
confidence: 99%
“…In the following we lift the Baykur-Korkmaz relation (a relation which is obtained from Equation (3.1) below by capping off the boundary circle δ 0 with a disk) to M 2 2 , and using this lift we improve the upper bounds for N (3,1) and N (4, 1). This result was predicted by Hamada and a sketch is given in [12].…”
Section: Theorem 31 ([12]) For the Minimal Numbermentioning
confidence: 99%
See 1 more Smart Citation
“…Two ingredients in this simple construction are suitable partial conjugations which effectively change the homology (e.g. [29,6,5]), and the explicit monodromy of a genus-1 open book with three binding components supporting the standard Stein fillable contact structure on T 3 (Lemma 1 and Proposition 2; also [34]). The small topology of these fillings will then allow us to show that many of these contact 3-manifolds admit symplectic Calabi-Yau caps introduced in [24], so as to conclude that they can not admit arbitrarily large Stein fillings (Theorem 7).…”
Section: Introductionmentioning
confidence: 99%
“…The value of N (g, h) has already been computed except N (g, 0) for g ≥ 3, N (g, 1) for g ≥ 2 and N (2,2). Recently Baykur and Korkmaz [1] found an interesting relation in the mapping class group M 1 2 of the genus-2 surface with one boundary component, and by using this relation they showed that N (2, 0) = 7. Furthermore, using the 8-holed torus relation [15] and the Matsumoto-Cadavid-Korkmaz relation [3,13,19], Hamada [12] found an upper bound for N (g, 1): he showed that N (g, 1) ≤ 4 if g ≥ 5 and N (g, 1) ≤ 6 if g = 3, 4.…”
mentioning
confidence: 97%